Country versus Industry Effects in Euro-Zone Corporate Performance - a Dynamic Approach - Koralun-Bereźnicka, Julia (Efekt kraju i sektora w kondycji finansowej przedsiębiorstw w ujęciu dynamicznym, 2010)
This study aims to compare the relative importance of industry and country factors in corporate performance within euro zone. Classification methods of clustering analysis were employed in order to verify whether the similarities between enterprises follow the country or the industry patterns more. The territory of the analysis was limited to nine euro-zone countries, which is a highly integrated area, and therefore fairly homogenous. Findings provide empirical evidence about the increasing role of industry factors in comparison with the previous findings. The main practical implication of the study is therefore the growing importance of cross-industry diversification strategies in comparison to the traditional cross-country investment diversification.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s. 71-87
Keywords: industry effect; country effect; corporate performance